2022
DOI: 10.1097/ico.0000000000003090
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Evaluation of Microblepharoexfoliation BlephEx as Adjunctive Therapy in the Treatment of Chalazia

Abstract: Purpose: Chalazia are benign eyelid lesions caused by the obstruction and inflammatory reaction of the meibomian glands. Demodex mites are one potential cause of chalazia leading to mechanical obstruction of the meibomian gland. In this prospective randomized study, we examine a novel approach to treating chalazia with the use of microblepharoexfoliation (MBE), an in-office lid hygiene technique that exfoliates the eyelid margins.Methods: Fifty patients with clinical evidence of acute chalazion were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, in the other study (n = 50), microblepharoexfoliation with terpinen-4-ol-formulated ocular wipe scrubs or sham scrubs was effective in reducing Demodex counts but not in improving the OSDI score or meibomian gland secretion or dropout [71]. A separate study of 50 patients reported effectiveness of microblepharoexfoliation in conjunction with traditional lid hygiene versus lid hygiene alone in significantly resolving chalazia [104].…”
Section: Microblepharoexfoliationmentioning
confidence: 90%
“…However, in the other study (n = 50), microblepharoexfoliation with terpinen-4-ol-formulated ocular wipe scrubs or sham scrubs was effective in reducing Demodex counts but not in improving the OSDI score or meibomian gland secretion or dropout [71]. A separate study of 50 patients reported effectiveness of microblepharoexfoliation in conjunction with traditional lid hygiene versus lid hygiene alone in significantly resolving chalazia [104].…”
Section: Microblepharoexfoliationmentioning
confidence: 90%
“…The data from each study were collected and summarized independently in tables designed by 2 researchers. The following information was obtained from each article: (1) author and date of publication (year), (2) study design, (3) 36,37 ; (5) meibomian gland secretions (MGS, grading from 0 to 4, where grade 0 is no expression, grade 1 is "ropy" meibum, grade 2 is turbid and viscous oil appearance, grade 3 is turbid oil, and grade 4 is normal meibum) 38 ; (6) meibomian glands yielding liquid secretions (MGYLS; defined as the number of MGYLS, values ranging from 0 to 15) 38 ; (7) microorganism load (reported as Demodex folliculorum count or gram-positive cocci and rods recorded as colony-forming units per swab) 10,39 ; (8) lipase activity [defined as the clearance zones in the tributyrin agar after overnight incubation, expressed in millimeters] 10 ; (9) Contact Lens Dry Eye Questionnaire-8 (CLDEQ-8, values ranging from 0 to 37) 40 ; and finally (10) author's opinion expressed by commenting in favor or against of eyelid exfoliation treatment. Baseline and end-offollow-up values for all these variables were collected in the treatment (T) and control (C) groups.…”
Section: Quality Assessment and Data Extractionmentioning
confidence: 99%
“…Eyelid exfoliation is a novel in-office treatment that works by cleaning the eyelashes and exfoliating the eyelid margins to remove the accumulated biofilm debris, epithelial keratinization, and capped meibomian glands, resulting in better meibum outflow. 1 This treatment may be known as microblepharoexfoliation (MBE) or eyelid debridementscaling (LDS) when it is performed with the BlephEx instrument (BlephEx LLC) or the stainless-steel golf club spud (Hilco Wilson Ophthalmics), respectively. Currently, evidence suggests that all forms of dry eye disease (DED) have an evaporative component because ocular surface hyperosmolarity can only arise in response to evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Its complexity is highlighted in its recent definition: ''a multifactorial disease of the ocular surface characterized by a loss of homeostasis of the tear film, accompanied by ocular symptoms, where tear film instability and hyperosmolarity, ocular surface inflammation and damage, and neurosensory abnormalities play etiological roles'' [3]. Significant innovations in DED treatment have emerged in the past decade, including new topical agents and mechanical and thermal therapies for meibomian gland dysfunction [4][5][6]. These advancements have broadened the therapeutic scope, allowing clinicians to offer more personalized and patient-centric care.…”
Section: Introductionmentioning
confidence: 99%